Pendekatan Diagnostik dan Terapi dengan Esofagoskopi di RSUP Prof. Dr. R. D. Kandou Manado Periode 2020-2024 - Mokoginta, Nabilla F.; Mengko, Steward K.; Mona, Moudi M. (Medical Scope Journal, 2025)
Abstract: Various abnormalities can be detected through esophagoscopy such as stricture, esophagitis, foreign body evaluation and malignancy. Moreover, the important role of esophagoscopy in treatment such as foreign body extraction, stricture dilatation and follow-up treatment plan based on the esophagoscopy results. This study aimed to determine the diagnostic and therapeutic approaches utilizing esophagoscopy at Prof. Dr. R. D. Kandou Hospital, Manado. This was a descriptive and retrospective study, using electronic medical records of patients who underwent esophagoscopy at Prof. Dr. R. D. Kandou Hospital Manado during the 2020-2024 period. The results showed that from 91 samples, 59% were male patients and 41% were female; most aged ≥51 years (46%). The most common symptoms experienced by patients were dysphagia (36%) and odynophagia (32%). Rigid esophagoscopy was predominantly used as a therapeutic approach, with the most frequent indication was foreign body extraction (78%), particularly coins (30%). Flexible esophagoscopy specifically esophagogastroduodenoscopy (EGD) was commonly used as a diagnostic approach with esophagitis being the most prevalent indication (67%). In conclusion, male patients were more often performed esophagoscopy on them, aged ≥51 years. The most common symptoms were feeling of blockage and pain in the throat. The most common indication for therapy was extraction of coins using rigid esophagoscopy. Esophagitis was the most common diagnostic indication obtained using EGD. Keywords: esophagoscopy; diagnostic approach; therapeutic approach Abstrak: Berbagai kelainan dapat dideteksi melalui esofagoskopi seperti striktur, esofagitis, evaluasi benda asing, dan keganasan. Peranan penting esofagoskopi dalam terapi seperti ekstraksi benda asing, dilatasi striktur dan rencana terapi lanjutan berdasarkan hasil esofagoskopi. Penelitian ini bertujuan untuk mengetahui pendekatan diagnostik dan terapi dengan esofagoskopi di RSUP Prof. Dr. R. D. Kandou Manado. Metode penelitian ialah deskriptif retrospektif, menggunakan data rekam medis elektronik pasien yang dilakukan esofagoskopi di RSUP Prof. Dr. R. D. Kandou Manado periode 2020-2024. Hasil penelitian mendapatkan dari total 91 sampel penelitian, 59% diantaranya merupakan pasien laki-laki dan 41% pasien perempuan, terbanyak berusia ≥51 tahun (46%). Gejala tersering yang dikeluhkan ialah disfagia (36%) dan odinofagia (32%). Esofagoskopi kaku paling sering digunakan sebagai pendekatan terapi dengan indikasi tersering ekstraksi benda asing (78%), jenis benda asing tersering yaitu uang logam (30%). Esofagoskopi lentur jenis EGD lebih sering digunakan untuk pendekatan diagnostik dengan indikasi terbanyak yaitu esofagitis (67%). Simpulan penelitian ini ialah mayoritas pasien laki-laki lebih sering dilakukan esofagoskopi, usia ≥51 tahun, gejala tersering ialah rasa mengganjal dan nyeri di tenggorokan, indikasi terapi paling sering dilakukan yaitu ekstraksi benda asing jenis uang logam menggunakan esofagoskopi kaku, dan esofagitis merupakan indikasi diagnostik tersering yang didapatkan menggunakan esofagoskopi lentur jenis EGD. Kata kunci: esofagoskopi; pendekatan diagnostic; pendekatan terapi